P13.14 Educating women about normal female genital appearance: the effectiveness of two brief interventions. (13th September 2015) - Sharp, G; Tiggemann, M
Abstract : Introduction: There has been a rapid increase in the demand for labial reduction surgery or labiaplasty in recent years. Labiaplasty is commonly performed for aesthetic reasons, more specifically; patients desire a smooth vulvar surface with 'tucked in' labia minora. In general, women are not aware of the great diversity in normal female genital appearance and believe that the 'tucked in' look shown in the media is the norm. The current study aimed to educate women from the general Australian community about the large variation in normal female genital appearance in order to improve their knowledge and also their attitudes towards their own genital appearance. Methods: Two freely available online resources were employed as educational interventions. The first intervention involved viewing a photographic array of normal female genitals and the second consisted of a short video addressing the digital airbrushing of women's labia minora in media images. A sample of 136 women aged 18–49 years were randomly assigned to view the photographs, video, both the photographs and video, or neither. Results: It was found that the video intervention significantly increased women's perceptions of the diversity of female genital appearance, as well as their knowledge of the digital airbrushing of genital images. Although there was no effect of the interventions on women's attitudes towards their own genital appearance, women who viewed the video indicated they would assist other women with genital appearance concerns by educating them about the digital airbrushing of media images. Conclusion: The results suggest that health practitioners could potentially use this short video to educate women who are concerned about the normality of their genital appearance and are considering labiaplasty. Moreover, this video could be used in sexual education programs in schools with young girls to potentially prevent the development of genital appearance concerns as they mature. Disclosure of interest statement: Nothing to declare.